Political Discourse And Ideology Promoting - Ariton-Gelan, Cristina (Revista de Comunicare si Marketing [Comunications and Marketing Journal], 2013)
A communication situation is influenced by power structures that conventional speakers are placed or not. Early .70s recognizes the role of language in structuring social relations of power. Language ideology mediates a variety of social institutions, ideology can be seen as an important part in establishing and maintaining unequal power relations. Effects of power and ideology in the production of meaning are not always obvious, which is why we talk about de-mystification of speech by deciphering ideologies.
https://katalog.adlr.link/Record/ai-53-244654